#TITLE_ALTERNATIVE# - HARDIANTO GAJAH (NIM 12304037), NOVERDI
Conventional normal moveout (NMO) and stacking process enhances reflections having a particular moveout velocity, while attenuating events having different moveout velocities. This process also acts as dip filter that applied in CMP stack. In other words, NMO and stacking process enhances reflection having particular slopes, while attenuating reflection event having different slopes. This process will decrease lateral resolution of the resulting data. Dip moveout correction is the exact process to overcome that problem. This correction will produce zero offset trace. Thus, reflection events which will be stacked is independent to dip. F-K DMO, one of dip moveout correction methods that apply Fourier Transform from TWT vs offset domain to frequencyvs wavenumber domain. F-K DMO is accomplished with the following sequences: NMO correction-DMO correction-inverse NMO-velocity analysis. These sequences are applied iteratively until the minimum gap between current and previous velocity function gained. This dip moveout method is accurate for all offset and dip, using constant velocity assumption. F-K DMO corrected data will give zero offset trace by chosing stacking velocity accurately. Besides, smearing effect occurred in dipping-reflector will be too disappeared. But, for complex geology structures where lateral velocity variation exist, inaccuracy of F-K DMO happens in applications.